Metaoptics with Nonrelativistic Matter Waves. (23rd September 2012) - Taillandier-Loize, T.; Baudon, J.; Hamamda, M.; Dutier, G.; Bocvarski, V.; Boustimi, M.; Perales, F.; Ducloy, M.
Abstract : The counterpart of metamaterials in light optics for nonrelativistic matter waves governed by the Schrödinger equation can be found by transiently reversing the group velocity using a so called comoving potential. Possible applications to wave-packet dynamics, atom interferometry, and atom deceleration are described.